2013
DOI: 10.3174/ajnr.a3398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Laboratory and Multiple-Reader Interpretation of Angiographic Images on Follow-Up Outcomes of Coiled Cerebral Aneurysms: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND AND PURPOSE:Reported rates of recanalization following coil embolization vary widely across studies. Some confounders are known to affect outcomes but others remain questionable. In the current study, we assess differences in reported angiographic outcomes for cerebral aneurysms treated with coil embolization as a function of single vs multiple readers and site investigator vs core laboratory settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Similarly, the angiographic parameters were mainly assessed by operators and not within an independent centralized core laboratory. In a recent meta-analysis, Rezek et al 27 demonstrated that core laboratories tend to report higher rates of unfavorable outcomes compared with self-reporting centers. In our opinion, the results of angiographic outcomes reported with the WEB device should be analyzed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the angiographic parameters were mainly assessed by operators and not within an independent centralized core laboratory. In a recent meta-analysis, Rezek et al 27 demonstrated that core laboratories tend to report higher rates of unfavorable outcomes compared with self-reporting centers. In our opinion, the results of angiographic outcomes reported with the WEB device should be analyzed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of coiling literature reported a rate of 18% of such outcomes. 1 In an effort to improve long-term occlusion rates, a number of "modified," second-generation coil types have been developed and marketed. Numerous single-center case series have been published regarding outcomes for each of these second-generation coil types, including Matrix (Boston Scientific, Natick, Massachusetts), [2][3][4] HydroCoil (MicroVention, Tustin, California), [5][6][7] and Cerecyte coils (Codman Neurovascular, Raynham, Massachusetts).…”
mentioning
confidence: 99%
“…The impact of core laboratory evaluation of outcomes has previously been studied in cardiology and its superiority over operator readings suggested. [24][25][26][27][28] A recent systematic review and meta-analysis of the endovascular literature for cerebral aneurysms 19 found that studies that used an independent core laboratory reported higher numbers of unfavorable angiographic outcomes as compared with treating center evaluations, but the quality of evidence was low for the heterogeneity of the literature studies. The current study, which allowed direct comparison of individual cases from a randomized cohort instead of relying on literature reviews, adds additional evidence for the impact of core lab readings on reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…10,[16][17][18] However, the influence of core laboratory interpretation on outcomes for research purposes, compared with operator evaluations at the treating centers, remains poorly studied. 19,20 In the current study, we assessed the agreement between an independent core laboratory and the operators at the treating centers regarding angiographic outcomes in a recent randomized, controlled trial.…”
mentioning
confidence: 99%